Optimalisasi kinerja organisasi melalui gaya kepemimpinan yang efektif untuk mencapai kepuasan kerja: sebuah studi literatur - Wibowo, Frendy; Tjahjono , Heru Kurnianto (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2023)
The potential success of a business depends on its organizational performance, meaning its ability to implement strategies effectively to achieve institutional goals. This study aims to describe a number of studies regarding organizational performance through effective leadership styles to achieve job satisfaction. The research method uses a literature review system with the stages of data analysis compare, contrast, and criticize. The research results show that leaders play an integral role in both organizational success and employee performance. Leadership requires special skills and abilities that are useful in complex leadership situations. Social competence and emotional intelligence must exist in every organization, so that even if there is conflict or upheaval within the organization, employees can still be motivated to work at full capacity because they feel satisfaction at work. Organizations that are oriented towards improving organizational performance must be able to fulfill employee job satisfaction, which in turn helps stimulate better employee performance and improve organizational performance.